Infective endocarditis due to Haemophilus sputorum. Issue 12 (5th December 2022) - Costello, Varea H.; Robinson, Sara L.; Klusewitz, Seth; Surpris, Guy; Nahid, Md; Backlund, Michael G.
Abstract : Introduction. Haemophilus species are gram-negative, non-motile, facultative anaerobic coccobacilli in the larger family of Pasteurellaceae . Implicated in a variety of human diseases, Haemophilus species are also included in the 'HACEK' group of organisms, which are fastidious gram-negative bacteria, a well-described but uncommon cause of endocarditis. Among the Haemophilus species responsible for endocarditis, Haemophilus parainfluenzae is the most frequently isolated. However, novel species of Haemophilus have recently been described, and their clinical significance remains uncertain. Case presentation. A 35-year-old man was admitted to the hospital after presenting with a 3 month history of nightly fevers, night sweats and unintentional weight loss, with a new murmur detected on cardiac auscultation. Blood cultures returned positive for Haemophilus sputorum identified by matrix assisted laser desorption ionization – time of flight MS, and confirmed with whole genome sequencing. Echocardiography revealed the presence of an aortic valve vegetation, with aortic and mitral valve leaflet perforations. He was successfully treated with surgical bioprosthetic valve replacements and pathogen-directed antibiotics without complications. Conclusion. We describe a case of infective endocarditis due to H. sputorum, a newly identified Haemophilus species, which to the best of our knowledge has yet to be reported, and discuss the available literature regarding this organism.